2009
DOI: 10.1007/s10722-009-9430-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential resistance of switchgrass Panicum virgatum L. lines to fall armyworms Spodoptera frugiperda (J. E. Smith)

Abstract: Six cultivars of switchgrass Panicum virgatum L., a plant native to North America that has potential as a bioenergy source, were evaluated for resistance to feeding by the fall armyworm Spodoptera frugiperda (J. E. Smith). Although no mortality was noted, seedlings of the cultivar 'Trailblazer' and older plants of the cultivar 'Blackwell' were among the most resistant to feeding by S. frugiperda. Some field-collected samples from natural habitat were fed upon by S. frugiperda as readily as were the cultivars, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…As an example, in the related native warm-season perennial, buffalograss, Buchloë dactyloides (Nuttall) Engelmann, an emergence in multiple important pests was demonstrated with increased use of this species as a turfgrass [4,16]. Likewise, recent work has demonstrated that insect problems may occur, particularly as production increases [1,9,22,28]. In 2004, a poorly understood species, Blastobasis repartella (Dietz), was rediscovered, and appears to be a monophagous stem-borer restricted to switchgrass [1,28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As an example, in the related native warm-season perennial, buffalograss, Buchloë dactyloides (Nuttall) Engelmann, an emergence in multiple important pests was demonstrated with increased use of this species as a turfgrass [4,16]. Likewise, recent work has demonstrated that insect problems may occur, particularly as production increases [1,9,22,28]. In 2004, a poorly understood species, Blastobasis repartella (Dietz), was rediscovered, and appears to be a monophagous stem-borer restricted to switchgrass [1,28].…”
Section: Introductionmentioning
confidence: 99%
“…Four additional lepidopterans, Spodoptera frugiperda (J.E. Smith) [9,10,24,30], Mythimna unipuncta (Haworth) [29], Papaipema nebris (Guenée), and Haimbachia albescens Capps [31] have also been recently documented on various populations of switchgrass. Burd et al [6] demonstrated that multiple switchgrass populations are suitable hosts to several important cereal aphids including: Schizaphis graminum (Rondani) (greenbug), Rhopalosiphum padi (L.) (bird-cherry oat aphid), Rhopalosiphum maidis (Fitch) (corn leaf aphid), and Sipha flava (Forbes) (yellow sugarcane aphid).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential resistance to potential insect pests has been demonstrated in various switchgrass populations. Dowd and Johnson [12] found differential resistance among several octaploid switchgrass populations to Spodoptera frugiperda (J. E. Smith), with "Trailblazer" and "Blackwell" being the most resistant. Differential resistance was also demonstrated among four tetraploid switchgrass populations to two key aphid species, S. graminum and S. flava [26,27].…”
Section: Discussionmentioning
confidence: 99%